Dealing with minor illnesses: the link between primary care characteristics and First Aid Clinics' attendances - Andrea Donatini; Gianluca Fiorentini; Matteo Lippi Bruni; Irene Mammi; Cristina Ugolini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2014)
The reformulation of existing boundaries between primary and secondary care, in order to shift selected services traditionally provided by Emergency Departments to community-based alternatives has determined a variety of organisational solutions aimed at reducing the ED overcrowding. One innovative change has been the introduction of fast-track systems for minor injuries or illnesses, whereby community care providers are involved in order to divert patients away from EDs. These facilities offer an open-access service for patients not requiring hospital treatments, and may be staffed by nurses and/or primary care general practitioners operating within, or alongside, the ED. To date little research has been undertaken on such experiences. To fill this gap, we analyse a First-aid clinic (FaC) in the Italian city of Parma, consisting of a minor injury unit located alongside the teaching hospital's ED. We examine the link between the utilisation rates of the FaC and primary care characteristics, focusing on the main organisational features of the practices and estimating panel count data models for 2007-2010. Our main findings indicate that the younger cohorts are heavy users of the FaC and that the extension of practice opening hours significantly lowers the number of attendances, after controlling for GP's and practice's characteristics.
Keywords: I11; I18; C31; 330